Facile and versatile PDMS-glass capillary double emulsion formation device coupled with rapid purification toward microfluidic giant liposome generation - Mostafa Bakouei; Ali Kalantarifard; Indraja Sundara Raju; Tatiana Avsievich; Lauri Rannaste; Marjut Kreivi; Caglar Elbuken (Microsystems & Nanoengineering)
Abstract The exceptional ability of liposomes to mimic a cellular lipid membrane makes them invaluable tools in biomembrane studies and bottom-up synthetic biology. Microfluidics provides a promising toolkit for creating giant liposomes in a controlled manner. Nevertheless, challenges associated with the microfluidic formation of double emulsions, as precursors to giant liposomes, limit the full exploration of this potential. In this study, we propose a PDMS-glass capillary hybrid device as a facile and versatile tool for the formation of double emulsions which not only eliminates the need for selective surface treatment, a well-known problem with PDMS formation chips, but also provides fabrication simplicity and reusability compared to the glass-capillary formation chips. These advantages make the presented device a versatile tool for forming double emulsions with varying sizes (spanning two orders of magnitude in diameter), shell thickness, number of compartments, and choice of solvents. We achieved robust thin shell double emulsion formation by operating the hybrid chip in double dripping mode without performing hydrophilic/phobic treatment a priori. In addition, as an alternative to the conventional, time-consuming density-based separation method, a tandem separation chip is developed to deliver double emulsions free of any oil droplet contamination in a continuous and rapid manner without any need for operator handling. The applicability of the device was demonstrated by forming giant liposomes using the solvent extraction method. This easy-to-replicate, flexible, and reliable microfluidic platform for the formation and separation of double emulsion templates paves the way for the high-throughput microfluidic generation of giant liposomes and synthetic cells, opening exciting avenues for biomimetic research. The presented giant liposome assembly line features a novel treatment-free hybrid chip for double emulsion formation coupled with a high throughput separation chip for sample purification.